Neural circuits for stress-induced water drinking in relief of anxiety - Lan Tang; Run-Jie Wu; Hong-Yu Li; Hong-Rui Wei; Jing-Bo Duan; Qianqian Lou; Le-Xian Li; Xin-Lu Yang; Wei Gao; Min Zhu; Zhi Zhang; Sen Qun; et al. (Proceedings of the National Academy of Sciences, 2026)
Drinking water is a rapid, instinctive behavior of mammals following stress. The role of such stress-induced water drinking behavior and its neural mechanisms remain poorly known. Here, we identify two sequentially activated neural circuits that respectively mediate stress-induced drinking behavior and reward encoding, which collectively promote the extinction of anxiety-like behaviors in mice. Specifically, mild short-term stress induces anxiety-like behaviors and activates glutamatergic neurons in the medial prefrontal cortex (mPFC Glu ) projecting to glutamatergic neurons in the median preoptic nucleus (MnPO Glu ), consequently driving drinking behavior in mice. This drinking behavior subsequently activates GABAergic neurons in the MnPO (MnPO GABA ), which then inhibit GABAergic neurons in the ventral tegmental area (VTA GABA ), leading to disinhibition of reward-encoding dopaminergic VTA neurons (VTA DA ), ultimately mediating the extinction of stress-induced anxiety-like behaviors. The present study defines cortical–hypothalamic–midbrain connections underlying the anxiety-relieving effects of drinking behavior, providing a circuit basis for innate stress coping strategies.